Review of Material Properties of Oxide Semiconductor Thin Films Grown by Atomic Layer Deposition for Next-Generation 3D Dynamic Random-Access Memory Devices - Choi, Ae Rim; Lim, Dong Hyun; Shin, So Yeon; Kang, Hye Joo; Kim, Dohee; Kim, Ja Yong; Ahn, Youngbae; Ryu, Seung Wook; Oh, Il Kwon (Chemistry of Materials, 2024)
Dynamic random-access memory (DRAM) devices are essential volatile memory components in most digital devices. With the increasing demand for further low-power and high-density devices, the planar structure of DRAM devices encountered a “memory wall”, ushering in an era of 3D DRAM architecture. InGaZnO-based thin-film transistors (IGZO TFTs) have a very low off current (<10-22 A/μm), representing a solution for new channel materials for next-generation 3D DRAM devices. IGZO TFTs are back-end-of-line (BEOL)-compatible, enabling them to move the DRAM peripheral circuitry under the memory array and integrate stacked DRAM cells. IGZO thin films have been widely studied for next-generation flat panel display applications. However, most studies have employed sputtering and solution-based systems, which hinder process compatibility in 3D DRAM devices with complex structures. Atomic layer deposition (ALD) is a viable alternative for solving these challenges. In this paper, we comprehensively review the reported Zn-, In-, Sn-, and Ga-based oxide semiconductors in terms of the ALD process (precursors, reactants, growth temperature, etc.), together with material properties such as purity, crystallinity, and electrical properties.
Keywords: Atomic-layer deposition; C. thin film transistor (TFT); Dynamic random access memory; High-density devices; Low Power; Low-high; Memory component; Planar structure; Semiconductors thin films; Volatile memory